Effect of tighter glycemic control on cardiac function, exercise capacity, and muscle strength in heart failure patients with type 2 diabetes: a randomized study. Issue 1 (29th April 2016) - Nielsen, Roni; Wiggers, Henrik; Thomsen, Henrik Holm; Bovin, Ann; Refsgaard, Jens; Abrahamsen, Jan; Møller, Niels; Bøtker, Hans Erik; Nørrelund, Helene
Abstract : Objectives: In patients with type 2 diabetes (T2D) and heart failure (HF), the optimal glycemic target is uncertain, and evidence-based data are lacking. Therefore, we performed a randomized study on the effect of optimized glycemic control on left ventricular function, exercise capacity, muscle strength, and body composition. Design and methods: 40 patients with T2D and HF (left ventricular ejection fraction (LVEF) 35±12% and hemoglobin A1c (HbA1c) 8.4±0.7% (68±0.8 mmol/mol)) were randomized to either 4-month optimization (OPT group) or non-optimization (non-OPT group) of glycemic control. Patients underwent dobutamine stress echocardiography, cardiopulmonary exercise test, 6 min hall-walk test (6-MWT), muscle strength examination, and dual X-ray absorptiometry scanning at baseline and at follow-up. Results: 39 patients completed the study. HbA1c decreased in the OPT versus the non-OPT group (8.4±0.8% (68±9 mmol/mol) to 7.6±0.7% (60±7 mmol/mol) vs 8.3±0.7% (67±10 mmol/mol) to 8.4±1.0% (68±11 mmol/mol); p<0.001). There was no difference between the groups with respect to changes in myocardial contractile reserve (LVEF (p=0.18)), oxygen consumption (p=0.55), exercise capacity (p=0.12), and 6-MWT (p=0.84). Muscle strength decreased in the non-OPT compared with the OPT group (37.2±8.1 to 34.8±8.3 kg vs 34.9±10.2 to 35.4±10.7 kg; p=0.01), in line with a non-significant decrease in lean (p=0.07) and fat (p=0.07) tissue mass in the non-OPT group. Hypoglycemia and fluid retention did not differ between groups. Conclusions: 4 months of optimization of glycemic control was associated with preserved muscle strength and lean body mass in patients with T2D and HF compared with lenient control, and had no deleterious effect on left ventricular contractile function and seemed to be safe. Trial registration number: NCT01213784; pre-results.